M40 Tackling Poor Attendance To Tuberculosis Clinic – Who, Why And What Can Be Done. (10th November 2014) - Denneny, EK; Black, SE; Bogle, Y; Macavei, VM; O'Shaughnessy, TC; White, VLC; Kunst, H; Jayasekera, NP
Abstract : Introduction: Despite efforts to improve Tuberculosis (TB) services, disease rates remain high (UK national average 14.4 per 100, 000). We believe one of the ongoing challenges is engaging patients in attending outpatient clinics for care. However, there is no current UK data evaluating poor attendance to TB clinic. Aim: To identify reasons for patient's not attending TB clinic, in order to implement service improvements and increase patient engagement. Methods: We conducted a prospective study reviewing the number of Did Not Attends (DNAs) to our TB clinic over a six-week period (April to June 2014). We evaluated data, usually obtained from patients who are contacted after they DNA, and cross referenced this with the trust electronic database. Data obtained included patient demographics, stage of TB treatment, route of referral, reasons for non-attendance and accessibility to clinic. Results: 63 of 385 patients (16% - 42 males, 21 females) did not attend their TB clinic appointments compared to 15% for non-TB respiratory appointments in this time. 64% were contactable (25 males, 15 females). Median age was 32 (range 17–78 years), which included 16 ethnicities and seven languages. 62.5% were follow-up appointments and 37.5% were new. 27.5% had TB previously. Stage of TB treatment included: completed (17.5%), current (25%), none (57.5%). Referral route included GP (40%), hospital (32.5%) and contact tracing (27.5%). 59% were aware of their appointment but were unable to attend due to other engagements. 41% stated they had not received a letter informing them of their appointment, 13% of these patients had relocated to another area and not updated their address. 8% of patients highlighted problems with transport leading to difficulties accessing the clinic. Conclusions: Communication to inform patients about appointments needs to be improved by both the referring and TB service. Utilising information technology and community links may improve patient education and therefore engagement with services. Experiencing the patient's journey will highlight further areas for development.